MES surfactant-based liquid soaps added with eco-enzyme and pandan wangi leaf extract (Pandanus amaryllifolius Roxb) on physical-chemistry properties, and antibacterial activity," - Riawati Riawati; Diah Mardiana; Arie Srihardyastutie (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
The growing demand for liquid soap has spurred innovations in soap formulations, particularly using methyl ester sulfonate (MES) as a surfactant base combined with natural ingredients like eco-enzyme and fragrant pandan leaf extract. This study aimed to determine the optimal liquid soap formulation by evaluating physicochemical properties and antibacterial activity against Staphylococcus aureus. The research was conducted in two stages. First, liquid soap was produced at different temperatures (20°C, 50°C, and 100°C) to identify the optimal temperature based on maximum lipase activity. In the second stage, various formulations were prepared, incorporating eco-enzyme and fragrant pandan leaf extract at the identified optimal temperature. The six formulations tested were: F1 (MES-based soap), F2 (20% eco-enzyme), F3 (15% eco-enzyme and 5% fragrant pandan leaf extract), F4 (10% eco-enzyme and 10% fragrant pandan leaf extract), F5 (5% eco-enzyme and 15% fragrant pandan leaf extract), and F6 (20% fragrant pandan leaf extract). The formulations were assessed for lipase activity, pH, density, and viscosity. The most effective formulation was further tested for antibacterial activity using the disc diffusion method with six treatments, including MES-based soap and controls. Statistical analysis using One-Way ANOVA revealed that adding eco-enzyme and fragrant pandan leaf extract significantly affected the soap's properties. The optimal formulation, containing 5% eco-enzyme and 15% fragrant pandan leaf extract, exhibited a lipase activity of 15,778 U/mL, a pH of 5.02, a density of 1.06 g/mL, a viscosity of 3.59 cP, and an antibacterial zone of 37.22 mm, making it the best candidate for further development